Five Essays on Asset Pricing - Časta, Martin; Pfeifer, Lukáš; Kočenda, Evžen, 1963-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This dissertation explores the relationship between macroeconomic and financial variables and their influence on asset pricing and financial market dynamics. The dissertation comprises five self-contained articles, each employing advanced econometric techniques to analyze how macro-financial variables affect asset pricing and market predictability. These articles are: (1) Recovery Theorem and Risk Aversion: Evidence from the Czech Republic; (2) Deriving the Equity Risk Premium Using Dividend Futures; (3) Inflation, Interest Rates, and the Predictability of Stock Returns; (4) Supply Shocks, Demand Shocks, and Yield Curve Dynamics; and (5) Forecasting Nominal Exchange Rates Using a Dynamic Model Averaging Framework. Collectively, these studies shed light on the roles of risk aversion, macroeconomic shocks, and expectation formation in the pricing of financial assets. All five articles have been published in peer-reviewed academic journals, including Finance Research Letters, The North American Journal of Economics and Finance, International Journal of Monetary Economics and Finance, and Heliyon. The overarching findings underscore the significance of intertemporal preferences and macroeconomic uncertainty in understanding the behavior of financial markets and improving predictive accuracy.
Vedoucí práce: Lukáš Pfeifer
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations